BF3-promoted electrochemical properties of quinoxaline in propylene carbonate1. Issue 24 (15th March 2015) - Carino, Emily V.; Diesendruck, Charles E.; Moore, Jeffrey S.; Curtiss, Larry A.; Assary, Rajeev S.; Brushett, Fikile R.
<x xml:space="preserve">Abstract</x> Electrochemical and density functional studies demonstrate that coordination of electrolyte constituents to quinoxalines modulates their electrochemical properties.